The Role of the Violence Prevention and Handling Team (TPPK) in Controlling Bullying at Elementary School 21 Pekanbaru - M. Wildan Alfarizi; Kasmanto Rinaldi (International Conference On Law And Social Sciences, 2024)
Bullying in schools is a complex and detrimental issue that can have negative impacts on the mental, emotional, and physical well-being of students. This problem involves aggressive behavior, intimidation, and repeated oppression by one individual or a group against another individual who is perceived as weaker or vulnerable. This research explores the role of the Violence Prevention and Handling Team (TPPK) in controlling bullying behavior at Elementary School 21 Pekanbaru. The research method employed is qualitative descriptive, involving interviews with informants. The research findings indicate that the consistency of educators, police counseling, the establishment of TPPK, and a positive school culture play significant roles in preventing student misconduct. These findings align with collaborative approaches and positive values within the school environment. These steps can serve as guidelines for other schools in their efforts to prevent student misconduct. The consistent involvement of educators, parents, police counseling activities, and the formation of TPPK have proven successful in preventing student misconduct. Collaboration among stakeholders, such as teachers, police, and the school team, has also proven effective in prevention efforts.